2022
DOI: 10.1186/s13030-022-00242-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep debt, social jetlag, and insomnia symptoms on presenteeism and psychological distress of workers in Japan: a cross-sectional study

Abstract: Background Presenteeism is an indicator of productivity loss and the risk of absence from work due to mental health problems. The purpose of this study was to determine the impact of sleep debt, social jetlag, and insomnia symptoms on presenteeism and psychological distress. Methods The participants were 351 Japanese workers (271 males, 79 females, and one of other gender, with a mean age of 49 ± 9.49 years). The eligibility criteria for this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The results, indicating that sleep debt is associated with presenteeism and low well-being, are consistent with those of previous studies [ 5 , 6 ]. The novelty of the current study results lies in the demonstration of various risks posed by sleep debt regardless of a full-time or part-time employment status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results, indicating that sleep debt is associated with presenteeism and low well-being, are consistent with those of previous studies [ 5 , 6 ]. The novelty of the current study results lies in the demonstration of various risks posed by sleep debt regardless of a full-time or part-time employment status.…”
Section: Discussionsupporting
confidence: 92%
“…Short and long sleep durations have also been shown to be associated with depression [ 4 ]. However, classification by absolute sleep duration may not reflect loss from the amount of sleep required by an individual; therefore, it is also necessary to evaluate sleep debt [ 5 ], which is linearly related to presenteeism and mental health [ 5 , 6 ]. As sleep duration was not appropriate for addressing correlations because of the U-shaped curve in relation to presenteeism and mental health, and because this U-shaped curve problem could be solved by using sleep debt [ 5 ], in the present study, sleep debt was used as a short sleep indicator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sleep behaviours, the cascading effect on psychological wellness was examined using EMA recordings, considering the close link between sleep problems and poor psychological wellness 9,10 . Appropriate sleep patterns are essential for promoting the quality of life of workers because several studies have reported an association between sleep problems and adverse occupational phenomena, such as presenteeism [11][12][13] , burnout syndrome 34 , low back pain 34,35 , and errors at work 36 . Furthermore, a report by the RAND Corporation estimated that sleep problems cost up to $680 billion annually in five OECD countries (Canada, Germany, Japan, the United States, and the United Kingdom) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep plays a key role in preventing adverse future health outcomes, such as coronary heart disease 1,2 , type Ⅱ diabetes [2][3][4] , and Alzheimer's disease 5,6 . In addition to being relevant to chronic diseases, sleep disturbance is associated with impaired psychological wellness, including psychiatric disorders 7,8 , disruption of daytime moods 9,10 , and affected work productivity (presenteeism) [11][12][13] and cognitive function 14,15 . In 2015, the National Sleep Foundation formulated age-specific sleep duration recommendations to prevent future health problems and recommended 7-9 hours of sleep for young adults and adults (18-64 years) 16 .…”
Section: Introductionmentioning
confidence: 99%